Klebsiella pneumoniae bacteremia mortality: a systematic review and meta-analysis - Li, Dan; Huang, Xiangning; Rao, Huayun; Yu, Hua; Long, Shanshan; Li, Yulian; Zhang, Jie (Frontiers in Cellular and Infection Microbiology, 2023)
Objective To analyze the mortality rate of patients with Klebsiella pneumoniae bacteremia (KPB) and the impact of extended spectrum beta-lactamase (ESBL) producing or carbapenem-resistance (CR) KP on the mortality rate among patients with bacteremia. Methods EMbase, Web of Science, PubMed, and The Cochrane Library were searched up to September 18th, 2022. Two reviewers independently extracted data and evaluated risk of bias of included studies by ROBINS-I tool. A meta-regression analysis was conducted using a mixed-effects model to explore possible sources of heterogeneity. A random-effects model was used for pooled analysis in case of significant heterogeneity (I2>50%). Otherwise, the fixed-effects model was performed. Results A total of 157 studies (37,915 enrolled patients) were included in the meta-analysis. The pooled death proportions of KPB were 17% (95% CI=0.14-0.20) at 7-day, 24% (95% CI=0.21-0.28) at 14-day, 29% (95% CI=0.26-0.31) at 30-day, 34% (95% CI=0.26-0.42) at 90-day, and 29% (95% CI=0.26-0.33) in hospital, respectively. Heterogeneity was found from the intensive care unit (ICU), hospital-acquired (HA), CRKP, and ESBL-KP in the meta-regression analysis. More than 50% of ICU, HA, CRKP, and ESBL-KP were associated with a significant higher 30-day mortality rates. The pooled mortality odds ratios (ORs) of CRKP vs. non-CRKP were 3.22 (95% CI 1.18-8.76) at 7-day, 5.66 (95% CI 4.31-7.42) at 14-day, 3.87 (95% CI 3.01-3.49) at 28- or 30-day, and 4.05 (95% CI 3.38-4.85) in hospital, respectively. Conclusions This meta-analysis indicated that patients with KPB in ICU, HA-KPB, CRKP, and ESBL-KP bacteremia were associated with a higher mortality rate. The high mortality rate caused by CRKP bacteremia has increased over time, challenging the public health.